FINANCING ANALYSIS OF SMALL AND MEDIUM ENTERPRISES USING MUDHÂRABAH CONTRACTS IN KOPERASI SIMPAN PINJAM AND SHARIA FINANCING BAIT AL-MÂL WA AL-TAMWÎL EL-TAQWA CIAMIS - Fitranty Adirestuty; Rini Irnawati; Yani Mulyani (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2020)
This study aims to analyze the financing of Micro, Small, and Medium Enterprises (MSMEs) using the mudhârabah contract provided by KSPPS-BMT eL-Taqwa Cidewa Ciamis. The mudhârabah financing product KSPPS-BMT eL-Taqwa Cidewa Ciamis is a solution for interest-based banks. This descriptive-qualitative research utilizes observation, interview, and document study techniques to obtain data information. The results showed that the implementation of the mudhârabah contract at KSPPS-BMT eL-Taqwa Cidewa Ciamis in determining the profit-sharing was adjusted to the understanding and requests of prospective customers. Two categories of profit-sharing are carried out, the profit-sharing ratio (%) for both parties is determined at the beginning of the contract before the income is known so that the monthly installment payments are fixed, and the profit-sharing ratio (%) is determined at the beginning of the agreement. Still, the installment payments are not fixed because adjusted to customer income. As for the role of the mudhârabah contract for micro, small and medium enterprises (MSMEs), of course, there are various kinds of developments experienced by every entrepreneur, seen from the good developments and some experiencing poor development so that they encounter obstacles in their business.